Effects of low voltage electrical stimulation on quality characteristics of young bulls fed to 14, 16 and 18 months of age - D.G. Gray; John A. Unruh; Curtis L. Kastner; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 1984)
Low voltage electrical stimulation of young bulls at 30 to 45 min after bleeding resulted in a lower muscle pH, higher marbling score, lighter cherry red color and reduced incidence of heat ring formation when compared to non-stimulated controls. Ribeye steaks from electrically stimulated sides were more tender than non-stimulated controls, but bottom round steaks were not different. Our results indicate that low voltage electrical stimulation, incorporated into a continuous slaughter operation as late as 30 to 45 min after bleeding, can improve USDA quality characteristics and tenderness of meat from young bulls.
Keywords: Cattlemen& #x27; s Day; 1984; Kansas Agricultural Experiment Station contribution; no. 84-300-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 448; Beef; Electrical stimulation; Quality; Bulls